Exercise Reverses Dysregulation of T-Cell-Related Function in Blood Leukocytes of Patients With Parkinson's Disease - Hu, Yong; Zhang, Kunshan; Zhang, Tianyu; Wang, Junbang; Chen, Fei; Qin, Wenting; Tong, Weifang; Guan, Qiang; He, Yijing; Gu, Chunya; Chen, Xiaoyu; Kang, Un Jung; et al. (Frontiers in Neurology, 2020)
Parkinson’s disease (PD) is a common neurodegenerative disease with movement and balance impairments. Though studies have reported improvement of motor symptoms with physical exercise, the mechanisms by which exercise is beneficial remains poorly understood. Our study addresses the exercise-induced changes to peripheral immune cells by interrogating the transcriptome of blood-derived leukocytes in PD patients before and after exercise. Patients attended 1-hour exercise classes twice a week for 12 weeks. Leukocytes were collected at the beginning and end of the study for gene expression analysis by RNA-seq or RT-qPCR. We correlated differentially expressed genes (DEGs) after exercise with clinical measures and analyzed the potential functions of gene changes with KEGG pathway and GO analysis. Exercise improved measures of movement and balance when compared with scores prior to the exercise program. Among the gene changes, KEGG and GO analysis suggests that T-cell receptor signaling, T-cell activation, and T-cell migration pathways were downregulated while the T-cell receptor signaling pathway was the most significantly correlated with clinical measures. To further investigate T-cell related changes in PD leukocytes, we re-analyzed the DEGs from publicly available microarray data and found that genes in the T-cell activation, differentiation, and migration pathways were up-regulated in PD samples compared to controls in a time-dependent manner. Together, our findings suggest that exercise rehabilitation may improve movement and balance in PD patients by reversing the upregulated T-cell activation pathways associated with PD. This study was registered with the Chinese Clinical Trial Registry under ChiCTR-TRC-14004707. Registered on May 27, 2014.